2018
DOI: 10.1002/admi.201800384
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Healing of Polymers via Supramolecular Chemistry

Abstract: rearrangements. While one challenge is to incorporate chemical modifications enabling chemical bond reformations, equally important is the coordination of chemical events with polymer network physical changes within interfacial regions resulting from mechanical damage.Recent studies suggested that two types of dynamic bonds are highly attractive to achieve self-healing in polymers: reversible covalent bonds and supramolecular chemistry. Reversible covalent bonds offer higher bonding energies, allowing the mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
117
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(125 citation statements)
references
References 173 publications
(145 reference statements)
1
117
0
1
Order By: Relevance
“…[ 20 ] Compared with extrinsic systems, intrinsically healable materials are usually flexible and deformable. [ 21,22 ] Therefore, intrinsic self‐healing polymers induced by supramolecular interaction [ 23,24 ] or reversible covalent bonds [ 25–27 ] could be ideal materials for self‐healing TENGs. The supramolecular systems are physically reversible based on non‐covalent interactions with rapidly exchanging.…”
Section: Introductionmentioning
confidence: 99%
“…[ 20 ] Compared with extrinsic systems, intrinsically healable materials are usually flexible and deformable. [ 21,22 ] Therefore, intrinsic self‐healing polymers induced by supramolecular interaction [ 23,24 ] or reversible covalent bonds [ 25–27 ] could be ideal materials for self‐healing TENGs. The supramolecular systems are physically reversible based on non‐covalent interactions with rapidly exchanging.…”
Section: Introductionmentioning
confidence: 99%
“…In this section, we summarize recent research progresses in the self‐healing function of different surface damage forms, such as cracks, scratches, punctures, and surface wear. In the past several years, there are some studies that are reported on self‐healing surface damages involving different materials, such as metal, ceramics, and polymers . In the following paragraphs, we will mainly concentrate on some relatively new progresses in self‐healing surface damages, and emphasize the intermolecular bonds formation and molecular chain mobility at damaged material interface.…”
Section: Self‐healing Of Different Surface Damage Formsmentioning
confidence: 99%
“…as metal, ceramics, and polymers. [53][54][55] In the following paragraphs, we will mainly concentrate on some relatively new progresses in self-healing surface damages, and emphasize the intermolecular bonds formation and molecular chain mobility at damaged material interface.…”
Section: Self-healing Of Different Surface Damage Formsmentioning
confidence: 99%
“…Collage of self‐healing materials addressed in the current Special Issue. Reproduced with permission …”
Section: Individual Contributions To the Special Issuementioning
confidence: 99%